Apoyo social percibido y factores sociodemográficos en relación con los síntomas de ansiedad, depresión y estrés en universitarios chilenos - Barrera Herrera, Ana; Neira-Cofré, Mariajosé; Raipán-Gómez, Paola; Riquelme-Lobos, Patricio; Escobar Alaniz, Bertha (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Perceived social support and socio-demographic factors in relation to symptoms of anxiety, depression and stress in Chilean university students. Research with university students shows a high prevalence of mental disorders, so it is necessary to study the impact of protective variables such as social support. The objective of this study was to determine the influence of perceived social support and the socio-demographic factors gender and socio-economical level on symptomatology related to depression, anxiety, and stress. In the framework of a non-experimental and cross-sectional design, 449 undergraduate students answered the Depression, Anxiety and Stress Scales (DASS-21) and the Multidimensional Scale of Perceived Social Support (MSPSS). Results showed that perceived social support was negatively associated with psychopathological symptoms, and that family support is the strongest predictor of mental health symptomatology. These findings indicate that family social support is important to Chilean university students and plays a protective role against the symptoms of anxiety, depression and stress in this stage in life. Keywords: emerging adulthood; perceived social support; depression; anxiety; stress. Resumen: Las investigaciones con universitarios evidencian alta prevalencia de trastornos mentales por lo que es necesario estudiar el impacto de variables protectoras como el apoyo social. El objetivo del estudio fue determinar la influencia del apoyo social percibido y de los factores sociodemográficos de género y nivel socioeconómico en la sintomatología depresiva, ansiosa y de estrés. En el marco de un diseño no experimental y transversal, 449 estudiantes universitarios respondieron las Escalas de Depresión, Ansiedad y Estrés (DASS-21) y la Escala Multidimensional de Apoyo Social Percibido (MSPSS). Los resultados mostraron que el apoyo social percibido se asocia de forma inversa a los síntomas psicopatológicos y que el apoyo familiar es el mejor predictor ante la aparición de sintomatología de salud mental. Los resultados confirman que los jóvenes chilenos otorgan importancia al apoyo social familiar, el cual cumple un rol protector ante los síntomas de ansiedad, depresión y estrés en esta etapa vital. Palabras clave: Adultez emergente; apoyo social percibido; depresión; ansiedad; estrés.